Genetic parameters and selection for multiple traits in recurrent selection populations of maize - Munique da Silva, Érica; Lisboa Guedes, Márcio; Crispim Filho, Ailton José; Ciappina, Angelina Luzia; Fialho dos Reis, Edésio; Pedroso Mendes Resende, Marcela (Revista Ceres, 2023)
The efficiency of recurrent selection depends, among other factors, on the estimation of parameters that guide the breeder to obtain genetic gains for multiple traits. The aim of this research was to estimate genetic and phenotypic parameters of maize populations during the third cycle of recurrent selection for traits of interest. The populations CRE-01 and CRE-02, potential for resistance to corn stunt, were described using genetic and phenotypic parameters of variance components, heritability, variation indices and correlation between 16 agronomic traits. Direct and indirect selection gains were estimated for each trait and considering the Smith and Hazel, Mulamba and Mock and Z index. Both populations have genetic variability for the traits. High heritability estimates were obtained for most of the traits, which associated with the genetic variability, indicate that these populations may show continuous gains with recurrent selection. All selection indexes provided satisfactory genetic gains, but the Z index was the most promising considering the results of both populations.